FACTORS AFFECTING COMMUNITY PATICIPATION IN THE WASTE BANK PROGRAM IN THE CITY OF SEMARANG - Melissa Azalea Gunawan; Mohammad Mirza Ansyori (SEAN Institute, 2023)
Waste management in developing countries still uses burning and open dumping methods. Likewise, in the City of Semarang, with an area of 373.7 Km2, 16 Districts, and 177, 1,200 tons of waste are released every day, and 438,000 tons of waste production every year. Regarding the volume of waste, the Head of the Semarang City Environment Service appealed to the people of Semarang City to be able to manage waste and activate the Garbage Bank in the city of Semarang. The research use quantitative methode, the sample of this study was 171 with multiple regression analysis using SPSS version 21 software. The results of research include there are significant effect between knowledge and attitudes to the engagement of community in the waste bank program. Moreover, there are no significant effect between education level, employment, attitudes, facility and benefit to the engagement of community in the waste bank program. Factors of knowledge, attitudes, education, employment, facilities, and important benefits in the engagement of community in the waste bank.